MERDEKA CURRICULUM: ASSESSMENT IMPLEMENTATION AND REPORTING SYSTEM AT MUJAHIDIN PONTIANAK PRIVATE HIGH SCHOOL - Imran Imran (Sean Institute, 2023)
This research was conducted to determine the assessment implementation and reporting system in one of the private schools in the city of Pontianak. The implementation of the independent curriculum is a curriculum modification process from the Minister of Education and is a complement to the 2013 curriculum and the emergency curriculum during the pandemic. The presence of an independent curriculum education system has differences in learning plans, implementation and assessment. It is not easy and quick to understand the system for teachers as facilitators for students. Thus, it is not surprising that schools that have just implemented the independent curriculum are still in the adaptation stage of carrying out independent curriculum assessments. This research question is to get an answer in the form of a description of the assessment implementation and reporting system at Mujahidin Pontianak Private High School, especially since the school has implemented an independent curriculum for less than one year or two semesters. This research method is descriptive qualitative. Data collection uses observation, interviews and documentation studies. The analysis according to Milles and Huberman. Based on the results of research on the assessment implementation system at SMAS Mujahidin in formative, namely to obtain information about student learning needs and four assessment processes consisting of categories (1) Need guidance, (2) Fairly good and (3) Very good. Summative is carried out at the end of each learning process, PTS and PAS. In the summative process, tasks are given to different students (differentiated learning). The KKTP of Mujahidin High School teachers is directed to use values ​​in the form of a range, such as 70-80, 81-90. Making KKTP, namely determining KKTP using criteria descriptions, determining KKTP using rubrics and determining KKTP using value intervals.